Relasi Gender dan Stereotype Perempuan sebagai Ibu Rumah Tangga dalam Iklan Soklin Liquid 2024 - Fadli, Hanif; Al-Azhar, Muhammad Fachrul Ikhsan; Rurian, Muhammad Arfan; Junaedi, Fajar (Jurnal Audiens, 2025)
This research aims to analyze gender relations and the stereotype of women as housewives in the Soklin Liquid 2024 advertisement. This research uses Roland Barthes' semiotic method to explore the representation of women through denotation, connotation, and myth. The theoretical framework of this research is based on the concepts of gender relations, stereotypes, and advertising to understand how social norms shape perceptions of women's roles. The research results show that this advertisement reinforces the traditional stereotype of women as housewives responsible for domestic tasks, such as doing laundry. Women are depicted wearing neat clothing, staying indoors, while men and children are shown enjoying leisure time outside the house. This representation maintains the view that women's primary role is limited to household tasks, reflecting existing cultural norms.